Monitoring of Electrical Energy during the Covid-19 Pandemic Using SMS on Microcontrollers - Muhammad Fitra Zambak (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
PT. PLN (Persero) has been getting prepaid and postpaid electricity program services, but in postpaid electricity programs, human errors often occur when officers read the kwh meter and PLN officials do not go down to residents' homes to record consumer usage due to the co-19 pandemic. In this research, an electrical energy monitoring tool was built using SMS (short massage service) based on the ATMEGA 2560 microcontroller that can measure and monitor the electrical energy consumption in real time using a voltage sensor and current sensor SCT013-030. The results of the current and voltage sensor readings will be forwarded to the ATMEGA 2560 microcontroller to be converted to the amount of electrical energy consumption and the amount of payment in accordance with the rates set by the PLN.